Prognostic factors for postoperative survival in melanoma patients with bone metastasis. Issue 4 (29th January 2021) - Wang, Yucheng; Ren, Shihong; Gong, Xiaokang; Wang, Jiacheng; Zhu, Ning; Cai, Danyang; Ruan, Jianwei
Abstract : Abstract: Melanoma can spread to the bone by metastasis and is relevant to a poor outcome. However, because of the rarity of melanoma patients with bone metastasis, the prognostic postoperative survival factors of them have not been elucidated. The aim of this special population-based cohort was to elucidate the prognostic factors associated with postoperative survival. The Surveillance, Epidemiology, and End Results database was used to extract postoperative survival data relating to patients with melanoma and bone metastasis at diagnosis between 2010 and 2016, along with data on a range of potential postoperative prognostic factors. We then investigated the potential postoperative prognostic roles of these factors using a Cox regression model and the Kaplan-Meier analysis. In all, the Surveillance, Epidemiology, and End Results database included 186 cases. Regarding overall survival, the 1-, 3-, and 5-year overall survival rates for the entire cohort were 36.2%, 15.4%, and 9.5%, respectively. Regarding cancer-specific survival, the 1-, 3-, and 5-year cancer-specific survival rates were 42.0%, 23.2%, and 16.6%, respectively. Within a cohort of melanoma patients with bone metastasis after surgery, our analysis showed that a smaller tumor size and the lack of metastases at other sites were predictors of survival.